Beyond Traditional Advertisements: Leveraging Facebook's Social Structures for Research Recruitment - Valdez, Rupa S; Guterbock, Thomas M; Thompson, Morgan J; Reilly, Jeremiah D; Menefee, Hannah K; Bennici, Maria S; Williams, Ishan C; Rexrode, Deborah L (JMIR Publications, 2014)
BackgroundObtaining access to a demographically and geographically diverse sample for health-related research can be costly and time consuming. Previous studies have reported mixed results regarding the potential of using social media-based advertisements to overcome these challenges. ObjectiveOur aim was to develop and assess the feasibility, benefits, and challenges of recruiting for research studies related to consumer health information technology (IT) by leveraging the social structures embedded in the social networking platform, Facebook. MethodsTwo recruitment strategies that involved direct communication with existing Facebook groups and pages were developed and implemented in two distinct populations. The first recruitment strategy involved posting a survey link directly to consenting groups and pages and was used to recruit Filipino-Americans to a study assessing the perceptions, use of, and preferences for consumer health IT. This study took place between August and December 2013. The second recruitment strategy targeted individuals with type 2 diabetes and involved creating a study-related Facebook group and asking administrators of other groups and pages to publicize our group to their members. Group members were then directly invited to participate in an online pre-study survey. This portion of a larger study to understand existing health management practices as a foundation for consumer health IT design took place between May and June 2014. In executing both recruitment strategies, efforts were made to establish trust and transparency. Recruitment rate, cost, content of interaction, and characteristics of the sample obtained were used to assess the recruitment methods. ResultsThe two recruitment methods yielded 87 and 79 complete responses, respectively. The first recruitment method yielded a rate of study completion proportionate to that of the rate of posts made, whereas recruitment successes of the second recruitment method seemed to follow directly from the actions of a subset of administrators. Excluding personnel time, the first recruitment method resulted in no direct costs, and the second recruitment method resulted in a total direct cost of US $118.17. Messages, posts, and comments received using both recruitment strategies reflected ten themes, including appreciation, assistance, clarification, concerns, encouragement, health information, interest, promotion, solicitations, and support. Both recruitment methods produced mixed results regarding sample representativeness with respect to characteristics such as gender, race, and ethnicity. ConclusionsThe results of the study demonstrate that leveraging the social structures of Facebook for health-related research was feasible for obtaining small samples appropriate for qualitative research but not for obtaining large samples needed for quantitative research. The content of interactions with members of the target population prompted ethical deliberations concerning suitable target communities and appropriate boundaries between researchers and participants. Widespread replication of this method would benefit from a broad discussion among researchers, social media users, social media companies, and experts in research ethics to address appropriate protocols for such interactions.